Adolescent Self-Disclosure in the Context of Interpersonal Relationships in the Digital Era - Kadek Nanda Osyana Putri Putri; Ni made Prasiwi Bestari (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The increase in the use of digital media by adolescents, which affects the way they express themselves and form social bonds, is a key driver of this study. The topic studied was the extent to which adolescent self-disclosure on social media affects interpersonal communication in the digital age. The purpose of this study is to understand the forms, factors, and impact of adolescent self-disclosure in digital interactions. Eight adolescents between the ages of 18 and 24 and a communication expert from the city of Denpasar participated in a qualitative study using phenomenological methods. In-depth interviews, observations, and documentation studies were used to collect data. Research shows that teens selectively disclose personal information by considering the boundaries of privacy, emotional closeness, and trust. Self-disclosure helps increase interpersonal trust and foster positive social relationships. In conclusion, adolescent self-disclosure in the digital era is a form of adaptation of modern interpersonal communication that emphasizes the balance between social obligations, self-expression, and self-control.